Percursos de autoria de professores no ensino tecnológico - Santos, Antonio Paulino dos (2017)
This work has a qualitative character and the intention to investigate the episodes that are possible to be narrated about the authorship of the researcher and other actors (teachers of IFAM campus Lábrea) when they tell about their teacher stories, which generates the need for those to narrate episodes about the paths derived from their teacher stories. In order to achieve this general objective, information related to the period in which I acted as a teacher will be systematized, highlighting important episodes during the course of authorship, considering the specificities of my home city, and will be narrated and presented the authorship courses of professors who work at IFAM campus Lábrea. At the first moment, a proper bibliographic review will be carried out on authorship paths. Then the researcher will systematize his remarkable episodes through his memoirs, with documents, photographs, excerpts of texts, among others (autobiographical narrative). The narratives of the other subjects will be obtained from recorded conversation wheels, the texts being transcribed and made points and counterpoints between the paths of the researcher and the other subjects, evidencing the proper discourse analysis, which may, in addition to generating documentation for the subject IFAM campus Lábrea; the re-signification of the pedagogical practices of teachers and subsidize a proposal of a short course with a dissertation product, which will allow teachers of Technological Teaching and readers in general to see authors of their own stories.